2016
DOI: 10.1002/acp.3270
|View full text |Cite
|
Sign up to set email alerts
|

Using the Model Statement to Elicit Information and Cues to Deceit from Native Speakers, Non‐native Speakers and Those Talking Through an Interpreter

Abstract: We examined how the presence of an interpreter during an interview affects eliciting information and cues to deceit, whilst using a method that encourages interviewees to provide more detail (model statement, MS). Sixty native English speakers were interviewed in English, and 186 non-native English speakers were interviewed in English or through an interpreter. Interviewees either lied or told the truth about a mock security meeting, which they reported twice: in an initial free recall and after listening to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 58 publications
(98 citation statements)
references
References 33 publications
8
88
1
Order By: Relevance
“…A consistent finding in these experiments is that when interviewees speak in their own language through an interpreter, fewer details are provided than when interviewees speak in their own language without an interpreter (Ewens, Vrij, Leal, Mann, Jo, & Fisher, 2016;Ewens et al, 2017;Ewens, Vrij, Leal, Mann, Jo, Shaboltas, 2016;Vrij, Leal, et al, 2017). Ewens, Vrij, Leal, Mann, Jo, Shaboltas, et al (2016) found evidence for two explanations. First, interpreters did not translate every detail that the interviewee gave.…”
Section: The Use Of An Interpretersupporting
confidence: 48%
See 3 more Smart Citations
“…A consistent finding in these experiments is that when interviewees speak in their own language through an interpreter, fewer details are provided than when interviewees speak in their own language without an interpreter (Ewens, Vrij, Leal, Mann, Jo, & Fisher, 2016;Ewens et al, 2017;Ewens, Vrij, Leal, Mann, Jo, Shaboltas, 2016;Vrij, Leal, et al, 2017). Ewens, Vrij, Leal, Mann, Jo, Shaboltas, et al (2016) found evidence for two explanations. First, interpreters did not translate every detail that the interviewee gave.…”
Section: The Use Of An Interpretersupporting
confidence: 48%
“…We are aware of only six experimental studies published in this area (Ewens, Vrij, Leal, Mann, Jo, & Fisher, 2016;Ewens et al, 2017;Ewens, Vrij, Leal, Mann, Jo, Shaboltas, 2016;Houston, Russano, & Ricks, 2017;Vrij, et al, in press;Vrij, Leal, et al, 2017). A consistent finding in these experiments is that when interviewees speak in their own language through an interpreter, fewer details are provided than when interviewees speak in their own language without an interpreter (Ewens, Vrij, Leal, Mann, Jo, & Fisher, 2016;Ewens et al, 2017;Ewens, Vrij, Leal, Mann, Jo, Shaboltas, 2016;Vrij, Leal, et al, 2017).…”
Section: The Use Of An Interpretermentioning
confidence: 82%
See 2 more Smart Citations
“…A Model Statement is a detailed example of an account unrelated to the topic of investigation (Leal et al ., ). Exposing interviewees to a Model Statement works as a social comparison (Festinger, ) and raises the expectations amongst interviewees about how much information they are expected to report (Ewens et al ., ). It raises such expectations in truth tellers as well as liars, with the result that both groups report a similar amount of extra detail after being exposed to a Model Statement (Vrij, Leal, & Fisher, ).…”
Section: Introductionmentioning
confidence: 99%